2010
DOI: 10.1590/s1516-35982010001100025
|View full text |Cite
|
Sign up to set email alerts
|

Profile of ingested fatty acids and in the duodenal digest of steers fed different diets

Abstract: -It was evaluated in this study the effect of the type of the diet on duodenal flow of long-chain fatty acids in steers. The tested diets were the following: conventional (feedlot diet composed of 60% corn silage and 40% of concentrate); winter forage silage -rye grass (Lolium multiflorum, Lam); or tropical forage silage -association of millet (Pennisetum americanum, Leeke + alexander grass, Brachiaria plantaginea). Six Charolais × Nellore crossbred steers with cannulas in duodenum were used in a 3 × 3 double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…A factor that may have contributed to reduce the w-6/w-3 ratio in treatments without supplementation and with 0.5 concentrate supplementation (Table 4) was the high content of linolenic acid (C18: 3 n-3) in pearl millet (22.74 g 100g -1 of total lipids of forage). In their study, Menezes et al (2010) found that animals fed a restricted diet with tropical pasture silage (pearl millet + Alexander grass) ingested a higher amount of omega-3 fatty acids (9.5 g per day) compared to those fed ryegrass silage (3.43 g d -1 ) or a diet containing 60% corn silage and 40% concentrate (5.89 g d -1 ), and showed relations omega-6:omega-3, 1.55, 1.13 and 5.72, respectively.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…A factor that may have contributed to reduce the w-6/w-3 ratio in treatments without supplementation and with 0.5 concentrate supplementation (Table 4) was the high content of linolenic acid (C18: 3 n-3) in pearl millet (22.74 g 100g -1 of total lipids of forage). In their study, Menezes et al (2010) found that animals fed a restricted diet with tropical pasture silage (pearl millet + Alexander grass) ingested a higher amount of omega-3 fatty acids (9.5 g per day) compared to those fed ryegrass silage (3.43 g d -1 ) or a diet containing 60% corn silage and 40% concentrate (5.89 g d -1 ), and showed relations omega-6:omega-3, 1.55, 1.13 and 5.72, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Using stored forage, Menezes et al (2010) observed that the consumption of pearl millet silage, compared to annual ryegrass silage, promotes a higher intake of SFA; however, the total of SFA that reaches the small intestine for absorption is similar. This may explain the insignificant change in the levels of SFA in meat from cattle, in the present and in other studies, such as that by Prado et al (2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding grain-based feeding, the biohydrogenation process was found to be inhibited by a decrease in the ruminal pH and ultimately growth inhibition of the CLA-producing bacteria (Wood et al, 2008) (Figure 1B). The reduction in the pH values is typically linked with this sort of diet, as the presence of concentrated food components reduces lipolysis, which is a fundamental step in biohydrogenation (Menezes et al, 2010). If ruminal biohydrogenation of UFA can be controlled, it may be possible to enhance the quality of ruminant meats via generally increasing UFA, CLA, and n-3 FAs in particular.…”
Section: The Impacts Of Grass-based Versus Grain-based Feeding On Thementioning
confidence: 99%